The effect of magnetization on the leached limonitic ore - , Pramusanto; Saleh, Nuryadi; Purwanto, Hadi (R&D Center for Mineral and Coal Technology, Indonesia, 2009)
In the viewpoint of environment preservation and efficient utilization of resources, a series process has been developed to utilize limonitic ore. Limonite is mineral content in laterite sediment with low Ni content and nickel laterite mining waste that can be an alternative raw material of iron making due to its high iron content. Upgrading of the ore was started with magnetization using mixed carbon monoxide and carbon dioxide, methane gases, as well as coal at desired temperature, then followed by leaching of the magnetized sample in sulphuric acid media. The result indicated that magnetization can speed up the nickel dissolution and obstruct the iron dissolution. The dissolution rate of nickel was very high in the initial period of less than 5 min, which reached almost half of the total recoverable nickel 95% for magnetized sample compared to the untreated one which remains 5.5%. The nickel dissolution would be higher by adding the leaching time. However, leaching time would not increase the dissolution of both nickel and iron in the non-magnetized sample. Accordingly, magnetization of the ore can control the non metallic dissolution in the leaching process such as iron oxide. At the end of the leaching process, there will be iron-rich residue with minimal nickel content and nickel-rich solution.